Drifting to absolutism ? - King, F. C. (Statistical and Social Inquiry Society of Ireland, 1953)
Thirty years ago, more or less, we attained our independence as a nation and proceeded to set up our own government with high hopes for our island territory both within and beyond the dividing frontier which cuts across it. We were free to form our own institutions, to build up our liberties in our own way, to fix limits to the intervention of the State in our daily lives, to establish the methods and the procedure of our government, to give ourselves our own Constitution. It is true that we were utterly untrained and inexperienced in the ways of national self-government and that our acquaintance with local self-government was very short and very chequered. This lack of experience made the task of laying the foundations of the State difficult and the additional complication of a civil war did nothing to lighten the burden of the constitution makers. When we look back on those beginnings the marvel is, not that there should be found much to criticise in the forms of government then adopted, but that a system should have been evolved which has given stability and which has survived in its fundamentals, to this day.
Read before the Society, 30 October 1952
Keywords: Absolutism, Ireland; Size and scope of government; Irish government; Democracy, Ireland; 314.15